Visible to near infrared conversion in Ce3+-Yb3+ Co-doped YAG ceramics - Ueda, Jumpei; Tanabe, Setsuhisa (Journal of Applied Physics, 2009)
In Ce3+–Yb3+ co-doped Y3Al5O12 (YAG) ceramics, possibility of quantum cutting mechanism converting one visible photon into two NIR photons with optimum quantum efficiency approaching 200% have been investigated. In this material, Yb3+ emissions due to the 2F5/2-2F7/2 in the range of 1 μm were observed upon the excitation of 5d level of Ce3+. In addition, excitation spectra of Yb3+ emission corresponded to that of Ce3+ emission completely. Lifetime of the 5d level of Ce3+ decreased with increasing Yb3+ content. These results indicate the energy transfer (ET) from the 5d levels of Ce3+ to the 5F5/2 level of Yb3+. In (Y0.945Ce0.005Yb0.05) 3Al5O12 sample, the directly measured quantum yield (QY) of Yb3+ emission upon the excitation of 5d level of Ce3+ was about 12% and lower than QY (96%) that estimated from the ET efficiency which was calculated with the measured lifetime of Ce3+.